ASSOCIATION OF VITAMIN D DEFICIENCY TO SEVERITY OF COVID-19 : A SYSTEMATIC REVIEW - Rossiyah, Nella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
As a pathogen invades, phagocytes quickly respond, but the adaptive immune response is more specific. Antigen-recognizing cytotoxic T cells control this immunological response. Cytotoxic T cells kill infection. These cells participate in humoral, antiparasitic, and antiviral immune responses. Balanced nutrition helps the immune system fight infections and neoplastic cells. Research describes how the immune system and defensive mechanisms defend the body from invaders, especially with optimal diet. Respiratory tract infections can worsen chronic diseases, increasing mortality. Vitamin D reduces respiratory infections, including pneumonia, through numerous mechanisms. UVB exposure converts 7-dehydrocholesterol into fat-soluble vitamin D. The liver converts it to 25(OH)D, which the kidneys or other organs convert to calcitriol 1, 25(OHD). Bones and teeth need vitamin D. Vitamin D aids bone metabolism, gastrointestinal calcium and phosphorus absorption, and the immune system, according to in vitro research. Most studies indicate COVID-19 severity with vitamin D levels below 12. Vitamin D pills benefit COVID-19 patients.